A Critical Review of Zinc Oxide Nanoparticles: Synthesis Strategies, Doping Chemistry, Structure–Property Correlations and Nanoscale Toxicological Considerations - Donna Patrick Prim; Priyanka Desai; Jay Rai (International Journal of Scientific Research in Science and Technology, 2026)
Zinc oxide (ZnO) nanoparticles are technologically significant class of metal oxide nanomaterials, whose optical, electronic, and the surface properties are strongly governed by size, morphology, crystal defects, and the elemental doping. Controlled synthesis and dopant incorporation play a major role in shaping their performance at nanoscale. This critical review examines conventional chemical synthesis routes, like sol–gel, hydrothermal, solvothermal, precipitation along with green synthesis strategies using plant extracts, highlighting their effect on the crystallinity, particle size, morphology, and defect chemistry. Also focusing on transition and non-transition-metal doping, with comparative discussion on dopant-induced lattice distortion, bandgap modulation, oxygen vacancy formation, surface reactivity, and structure–property correlations. Moreover, nanoscale toxicological considerations are addressed that highlights the dependence of ZnO nanoparticle toxicity on physicochemical parameters, exposure pathways, and dose. Current challenges in reproducibility, dopant control, and safety assessment are identified and are outlined for rational design of ZnO nanoparticles for nanotechnology-driven applications.
Keywords: Zinc oxide nanoparticles; Metal-doped ZnO; Reactive Oxygen Species; Nanoscale toxicity